Correlation between symptoms of depression, attitude, and self-care in elderly with type 2 diabetes - Maria Cristina Lins Oliveira Frazão; Lia Raquel de Carvalho Viana; Gerlania Rodrigues Salviano Ferreira; Cláudia Jeane Lopes Pimenta; Cleane Rosa Ribeiro da Silva; Kaisy Martins de Albuquerque Madruga; Patrícia Serpa de Souza Batista; Kátia Neyla de Freitas Macedo Costa (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to correlate depressive symptoms, attitude, and self-care of elderly people with type 2 diabetes. Methods: study developed with 144 elderly people with diabetes; carried out in Family Health Units. A semi-structured instrument was used to obtain data on the sociodemographic profile; the Geriatric Depression Scale (15 items), the Questionário de Atitudes Psicológicas do Diabetes [Psychological Attitudes of Diabetes Questionnaire], and the Diabetes Self-Care Activities Questionnaire (DSCA) were also used. Results: it was identified that 24.3% of the participants presented depressive symptoms, and 93.8% presented negative attitudes of coping. A greater adherence to self-care activities related to the practice of medication was observed. In the correlation between the scales, a negative and inversely proportional correspondence was noted between depressive symptomatology and physical activity (p=0.010) and foot care (p=0.006), likewise between attitude and foot care (p=0.009). Conclusions: self-care in elderly people with diabetes mellitus is influenced by depressive symptoms and negative coping attitudes.